Epitaxial Growth of High Efficiency Germanium Solar Cells by MOCVD - Kim, Youngjo (The Graduate School, Ajou University, 2016)
III-V compound semiconductor based multi-junction solar cells promise super high efficiencies because of the tandem structure consisting of monolithically stacked two or more subcells with different band gap. Recently, beyond 40% efficiencies have been achieved under concentrated illuminations. The III-V multi-junction solar cells have been used for space applications due to their high efficiency and resistance to the ionizing radiation in outer space. However, the III-V based solar cells are not suitable for terrestrial energy production because their device cost is relatively high. Although concentrator photovoltaic systems have been developed by using the III-V solar cells, they are still suffering from the higher cell cost compared to Si based photovoltaic systems. The most expensive cost driver is the Ge wafer for the commercial InGaP/InGaAs/Ge solar cell. Because the p-n junction of the Ge bottom cell is realized by atomic diffusion into a p-type Ge wafer, it is difficult to replace the Ge wafer with a cost effective alternative substrate. In this dissertation, epitaxial growth of Ge solar cells have been studied to investigate the possibility that Ge p-n junction can be realized on heterosubstrates such as GaAs and Si. If the Ge solar cell structure is successfully grown on GaAs, the InGaP/InGaAs/Ge solar cell structure can be realized on a GaAs substrate which can be reused by an epitaxial lift-off process. On the other hand, if high quality III-V/Ge layers are grown on Si, the Ge wafer can be replaced with a low cost Si substrate which is available with a large diameter over 300 mm. Therefore, the Ge epitaxy can be a key technology to reduce the device cost of the InGaP/InGaAs/Ge solar cell. First, single-junction Ge solar cells are grown by metalorganic chemical vapor deposition (MOCVD) on p-type Ge (001) substrates. Both phosphorus diffusion and epitaxial growth of an n-type Ge layer are investigated to realize high quality Ge p-n junction structures. The Ge epi-layer is grown by using an isobutylgermane (IBuGe) metalorganic source which is a novel Ge precursor. The single-junctnion Ge solar cells are fabricated by photolithography, metal evaporation, rapid thermal annealing, wet chemical etching, and back-end processes. Very high efficiencies of 10.68% and 11.70% can be achieved by the single-junction Ge solar cells realized by atomic diffusion and epitaxial growth methods, respectively. Furthermore, the device quality as a bottom cell is investigated by employing the Ge solar cell in an InGaAsNSb/Ge double-junction solar cell structure. Second, single-junction Ge solar cell structures are entirely grown on GaAs (001) substrates by MOCVD using IBuGe. Various growth conditions are investigated to reduce the doping level over 1×1019 cm-3 of the p-type Ge base layer, which is detrimental to the minority carrier collection efficiency. By increasing the growth rate and employing delta doping technique, the p-type doping level of the epitaxial Ge layer can be lowered to 2×1018 cm-3. As a result, the Ge solar cell epitaxially grown on GaAs substrate is reported with a high efficiency of 8.95%. Third, epitaxial Ge layers are grown on Si (001) substrates by MOCVD using IBuGe. Low and high temperature two-step growth and post annealing techniques are employed to overcome the lattice mismatch problem between Ge and Si. It is demonstrated that high quality Ge epitaxial layers can be grown on Si (001) with a surface rms roughness of 2 nm and an estimated threading dislocation density of 4.9×107 cm-2. Furthermore, the first Ge solar cell is realized on Si substrates by the in situ MOCVD growth. Finally, nanostructured single-junction Ge solar cells are investigated to achieve higher efficiencies. Hybrid radial and planar junction Ge solar cells are realized by surface nanopatterning and MOCVD growth techniques. The Ge nanopillar arrays are selectively patterned on Ge (100) substrates using a cost-effective nanosphere lithography. The radial and planar junctions are realized by the epitaxial growth of an n-type Ge emitter layer. It is demonstrated that the light absorption properties can be improved by employing the nanopillar and planar hybrid junction structures.
학위논문(박사)--아주대학교 일반대학원 :전자공학과,2016. 2
Keywords: solar cells; photovoltaics; multi-junction; tandem; efficiency; III-V compound semiconductors; germanium; isobutylgermane; epitaxial growth; MOCVD